Analysis of Public Policy Responses in China’s Urbanization Process from a Sustainable Development Perspective — Taking the Renovation of “Urban Villages” as an Example - He, Yinlin; Li, Jiayi (Studies in Social Science & Humanities, 2025)
The paper analyzes the public policy response to the renovation of urban villages from the perspective of sustainable development, facing the environmental, economic, social problems brought by the implementation of the renovation of urban villages, and put forward the strategy of optimizing the public policy through institutional innovation, financial tools and digital technology to promote more sustainable and integrated urban renewal.